Development of Discrepancy Evaluation Model based on Tat Twam Asi with TOPSIS Calculation - Divayana, Dewa Gede Hendra; Adiarta, Agus; Suyasa, P. Wayan Arta (International journal of advanced computer science & applications, 2022)
This research had the main objective to provide information related to the innovation available in the form of an educational evaluation model that integrates the Discrepancy evaluation component, Tat Twam Asi concept, and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method in the framework of determining the dominant indicators triggering the effectiveness of implementing blended learning in IT vocational schools. The approach of this research was development research by an R & D development model that focused on four stages, including a) research and field data collection, b) planning, c) design development, d) initial trial, and e) revisions to the results of the initial trial. There were 34 subjects involved in the trial design of the evaluation model in this research, including two education experts, two informatics experts, and 30 IT vocational teachers in Bali. The instruments used in data collection were in the form of questionnaires, interview guidelines, and photo documentation. The analysis technique for the data that had been collected used quantitative descriptive techniques that referred to percentage descriptive calculations. The results of this research were Tat Twam Asi-based Discrepancy evaluation model design which was integrated with TOPSIS calculations and had been classified as excellent according to the eleven-scale categorization table.